Book Review - Schmidheiny, Stephan; Zorraquin, Frederico J.L. ; Steel, Ronald; Bar-On, Mordechai (Tufts Archival Research Center, 2005)
Volume 21, Issue 1. Winter/Spring. Financing Change: The Financial Community, Eco-efficiency and Sustainable Development. Temptations of a Superpower. In Pursuit of Peace: A History of the Israeli Peace Movement. Book Review